Subsidiarity and the European Convention on Human Rights - Mowbray, Alastair (Oxford University Press, 2015)
Theoretical views on the concept of subsidiarity are examined followed by an analysis of the origins of the principle of subsidiarity within the ECHR. The Court’s utilisation of the principle, as disclosed by the jurisprudence, is studied across three time periods encompassing the original part-time Court, the first decade of the full-time Court and the post-Interlaken era. This is supplemented by a consideration of some quantitative data, derived from the Court’s HUDOC database, on the usage of subsidiarity in the case reports of Court judgments. Particular attention is given to Grand Chamber judgments since 2010. Overall conclusions are then drawn on, inter alia, whether the Court’s use of the principle has altered over time, whether the principle is simply a device to limit the authority of the Court, who can benefit from the application of the principle and what links may be made between the theoretical writings and the actual judgments delivered at Strasbourg.